Leveraging Innovative Technologies for Improved Library Practices in the Digital Era: The Nigerian Perspective. - Chidimma Ojobor, Rebecca; Okafor, Victoria N.; Ugwuanyi, Richard N. (Information Technology & Libraries, 2025)
Lack of expertise, among other reasons, has been cited as the reason for Nigerian libraries' sluggish adoption and application of innovative technology. To solve this problem, a thorough analysis of the level of technology implementation in Nigerian libraries is needed. This work closes the gap in the literature by using the PRISMA search method to examine 42 pertinent works published between 2016 and 2023. A questionnaire was used to collect data from 240 respondents using the survey approach. Six federal university libraries were selected by a stratified random sampling procedure, one from each of Nigeria's six geopolitical zones. Then, 40 library employees from each of the selected libraries were selected using a purposive sample technique. Mean and standard deviation were used to analyze the responses. The results demonstrate a grand mean of 2.44 (SD=1.15), indicating low staff awareness of the potential benefits of innovative technology for library operations. A negative grand mean of 2.42 on the degree of usage was also noted, indicating low use of cutting-edge technology in the research area. A lack of internet penetration, a deficiency of digital literacy, insufficient funds, and unstable power sources were among the problems found limiting Nigerian libraries from taking advantage of advanced technologies. In light of this, the study suggests that the Nigerian government should increase budget allocations for libraries and enhance policies that support the self-development of library staff. Additionally, libraries in developing countries should seek mentorship from those in developed nations to update their knowledge and skills, enabling better implementation and deployment of cutting-edge technology in their libraries.